Next-Generation Electrode Materials: La/Ce Doping for Superior Anodic Oxidation - Okur, Melike Ceren; Ozturk, Dilara; Akyol, Abdurrahman (Wiley-V C H Verlag Gmbh, 2024)
In this study, the characterization, optimization and effect of model compound Reactive Black 5 (RB5) dye on the process performance of lanthanum (La) and cerium (Ce) doped iridium-ruthenium (Ir-Ru) mixed metal oxide (MMO) electrodes were investigated. The electrodes had varying La and Ce doping levels at 5%, 10% and 20% concentrations and were coated by thermal decomposition technique. In addition, a mixed La/Ce electrode was prepared with 10% Ce and 10% La. This study focused on understanding the effects of La and Ce doping, pH, conductivity and concentration on the electrochemical degradation process. The experiments were conducted over various pH values (3, 5, 7 and 9), dye concentrations (50, 100, 300 and 500 ppm), current densities (100, 200, 350 and 600 A.m-2) and conductivities (1500, 3500, 5500 and 10000 mu S.cm-1). It was found that the newly developed electrode doped with 10% Ce and 10% La showed the most efficient results. This study provides insights into optimizing the operational parameters for effective electrochemical process with the novel La/Ce doped MMO electrodes.
Keywords: Ce doped electrode; Electrooxidation; Electrode coating; La doped electrode; Reactive Black 5